(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
A study on morphometrics, meristics sex ratio, ovary condition of Periophthalmodon schlosseri was conducted in 2001. The mean of total length (49.63 + 5.99 mm), standard length (40.84 + 5.30 mm), snout length (4.12 + 0.65 mm), head length (9.86 + 1.39 mm), height of body (6.89+1.24 mm) and the length of caudal peduncle (6.96 + 1.08 mm) were calculated. The length-weight relationship was determined as TW = 0.00004639+2.5882 TL. The fin formula was D1 . 8-9; D2 .1/10-13; P1 . 11-14; P2 . 11-14; A. 1/11. The sex ratio was found to be 1:0.63. The average of ovary length (6.2 +0.84 mm), ovary breadth (3.54 +0.95 mm) and diameter of ova (0.22 +0.04 mm) were also determined. Bangladesh J. Sci. Ind. Res. 47(4), 449-452, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14076